Hermann’s Jazz Club: Technological Challeneges for a Venue During the Pandemic - Stewart, William (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
William Stewart, the Technical Director of Hermann’s Jazz Club in Victoria, Canada, discusses the technological solutions he devised to continue to present jazz concerts online during the pandemic.